Hypothetical model of the development of a future teacher as a humanist (on the basis of humanitarian subjects) - Mussabekova, Gulnar; Issayeva, Kulaina; Oralova, Zаuresh; Saparbayeva, Uldanay; Faiziyev, Nurzhan; Mutaliyev, Bekarys (Opción, 2018)
The urgency of the development of teacher’s humanist personality is important due to fact that existing educational institutions do not fully meet the requirements of the socioeconomic development of the Republic of Kazakhstan. These disadvantages expressed as there is a uniformity of teaching in educational institutions, alienation from society and ethnic cultures is growing; the role of the development is weakened. As a result, we found that the students of pedagogical universities have different views on their knowledge of humanitarian subjects: majority of students rated their knowledge as average and low and only 27.9% of students rated their knowledge as high.